2019
DOI: 10.1002/hbm.24534
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared spectroscopy reveals neural perception of vocal emotions in human neonates

Abstract: Processing affective prosody, that is the emotional tone of a speaker, is fundamental to human communication and adaptive behaviors. Previous studies have mainly focused on adults and infants; thus the neural mechanisms underlying the processing of affective prosody in newborns remain unclear. Here, we used near‐infrared spectroscopy to examine the ability of 0‐to‐4‐day‐old neonates to discriminate emotions conveyed by speech prosody in their maternal language and a foreign language. Happy, fearful, and angry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 132 publications
3
21
1
Order By: Relevance
“…After the hearing is reconstructed, the auditory cortex receives better auditory stimulation. Because emotion recognition and positive bias could be observed in neonates as early as 0–4 days after birth in previous studies ( Zhang et al, 2019 ), we expected that ITCIs would respond to the four vocal emotional stimuli in 0–7 days after the CI is activated, and a stronger neural response will be observed in the right temporal area, with a positive bias. That is, happiness will cause stronger activation of the cortex than other vocal emotions.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…After the hearing is reconstructed, the auditory cortex receives better auditory stimulation. Because emotion recognition and positive bias could be observed in neonates as early as 0–4 days after birth in previous studies ( Zhang et al, 2019 ), we expected that ITCIs would respond to the four vocal emotional stimuli in 0–7 days after the CI is activated, and a stronger neural response will be observed in the right temporal area, with a positive bias. That is, happiness will cause stronger activation of the cortex than other vocal emotions.…”
Section: Introductionmentioning
confidence: 94%
“…Many studies have examined the neural processing for vocal emotions in infants with normal hearing, which may provide a reference for the neural processing associated with hearing loss. Information regarding the neural processing mechanism of vocal emotion was also reported in neonates ( Zhang et al, 2017 , 2019 ; Zhao et al, 2019 ). The results showed that vocal emotions enhance the activation of the right superior temporal gyrus (STG), the left superior frontal gyrus (SFG), and the left angular gyrus, which may indicate the regions associated with the neural processing of vocal emotional perception during neonatal development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, studies implementing emotion prosody tasks identified the temporal cortex as a key area of activation owing to its involvement in the auditory network ( Zhang et al. , 2017 , 2019 ; Zhao et al. , 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It reflects cerebral blood flow by measuring changes in ΔHbO 2 and ΔHb (Ferrari & Quaresima, 2012; Scholkmann et al., 2014). Studies have shown that changes in cerebral blood flow can be observed in neonates when stimulated by different emotional prosodies (Zhang et al., 2017, 2019), by comparing the response between healthy neonates and HIE neonates using event‐related potentials (ERP), studies have found an impaired ability to differentiate emotional prosodies in neonates with brain injuries (Sun et al., 2019), but ERP lacks spatial resolution for determining the brain region that is impaired in function.…”
Section: Introductionmentioning
confidence: 99%